Major merger fraction along the massive galaxy-quenching channel at 0.2 < z < 0.7 - Inoue, Shin; Ohta, Kouji; Asada, Yoshihisa; Sawicki, Marcin; Desprez, Guillaume; Gwyn, Stephen; Picouet, Vincent (Publications of the Astronomical Society of Japan, 2024)
We study the major merger fraction along the massive galaxy-quenching channel (traced with rest-frame $\mathrm{NUV}-r$ color) at z = 0.2–0.7, aiming to examine the cosmic web detachment (CWD) scenario of galaxy quenching. In this scenario, the major merger fraction is expected to be high in green-valley galaxies as compared with those in star-forming and quiescent galaxies of similar stellar mass. We used photometry in the E-COSMOS field to select 1491 (2334) massive ($M_\ast \\gt 10^{9.5}\, M_{\odot }$) galaxies with $m_i\\lt 22$ mag ($m_z\\lt 22$ mag) at z = 0.2–0.4 (z = 0.4–0.7) in the rest-frame color range of $0.8\\lt r-K_{\rm s}\\lt 1.3$. We define a major galaxy–galaxy merger as a galaxy pair of comparable angular size and luminosity with tidal tails or bridges, and we identified such major mergers through visual inspection of Subaru HSC-SSP PDR 2 i- and z-band images. We classify 92 (123) galaxies as major merger galaxies at z = 0.2–0.4 (z = 0.4–0.7). The resulting major merger fraction is 5%–6% and this fraction does not change with galaxy color along the massive galaxy-quenching channel. The result is not consistent with the expectation based of the CWD scenario as the dominant mechanism of massive galaxy quenching. However, there are some caveats such as (i) the mergers that cause quenching may lose their visible merger signatures rapidly before they enter the green valley, (ii) our method may not trace the cosmic web sufficiently well, and (iii) because of our mass limit, most of the galaxies in our sample may have already experienced CWD events at higher redshifts than those studied here. Further studies with deeper data are desirable in the future.